PENGARUH KOMPOS SERASAH DAUN KARET TERHADAP PERTUMBUHAN BIBIT KARET STUM MATA TIDUR DI MEDIA GAMBUT - ronald, Albertus; Sopiana, Sopiana; Jatsiyah, Venti (Politeknik Negeri Ketapang, 2023)
Efforts to overcome the problem of limited fertile soil is to utilize peat soil with compost treated with rubber leaf litter. The purpose of this study was to determine the effect of applying rubber leaf litter compost on the growth of sleeping eye stum rubber seeds in peat media. The result was conducted at the Ketapang State Polytechnic experimental garden, from April to July 2021. The study used a single factor Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatment used was K0 = 1000 g of peat soil, K1 = 300 g of rubber leaf litter compost + 700 g of peat soil, K2 = 400 g of rubber leaf litter compost + 600 g of peat soil and K3 = 500 g of rubber leaf litter compost + 500 g peat. The data obtained was analyzed statistically using Analysis of Variances (ANOVA) using the SAS application version 9.0. If it is significantly different, then proceed with the Duncan Multiple Range Test (DMRT) at the 5% level. The results showed that the application of rubber leaf litter compost had a significant effect on the growth of sleeping eye stum in peat media on the parameters of shoot length, stem diameter, number of umbrellas and root length. 500 g rubber leaf litter compost + 500 g peat soil is the best treatment to increase the growth of sleeping eye stum in peat media.